2014
DOI: 10.4236/ojpm.2014.46054
|View full text |Cite
|
Sign up to set email alerts
|

Health Status Inequality among Immigrants in Switzerland

Abstract: Objective: To assess self-rated health and impairments for six large immigrant groups (Germany, Italy, Kosovo, Portugal, Serbia, Turkey) in Switzerland. Methods: We used population-based survey data from the Swiss Migrant Health Survey 2010 and the Swiss Health Survey 2007. The sample comprised permanent residents aged 17 -64 years (n = 14,637). Multivariate logistic regressions have been used to estimate odds ratios (OR). Results: Ill health and activities of daily living (ADL) impairments were associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
6
1
1
Order By: Relevance
“…We chose the SHS 2012, instead of the most recent wave from 2017, as the former is only two instead of seven years apart from the most recent GMM II in 2010. GMM II has been combined before with SHS 2007 [ 5 ], but only the Swiss sub-sample was extracted. In contrast, we use the whole sample from the SHS, including all immigrants, and benefit from a smaller time distance between the two surveys.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose the SHS 2012, instead of the most recent wave from 2017, as the former is only two instead of seven years apart from the most recent GMM II in 2010. GMM II has been combined before with SHS 2007 [ 5 ], but only the Swiss sub-sample was extracted. In contrast, we use the whole sample from the SHS, including all immigrants, and benefit from a smaller time distance between the two surveys.…”
Section: Methodsmentioning
confidence: 99%
“…For asylum seekers, the mandatory basic health insurance is covered by the cantons (Federal Act of 18 March 1994 on Health Insurance). However, there is evidence that some immigrant groups tend to suffer higher rates of mortality and morbidity compared to non-migrants [ 5 , 17 ], which could be due to differences in the utilization of care [ 4 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immigrants may be very heterogeneous in some host countries and that the conventional Western conception of immigrants as vulnerable individuals characterized by low socio-economic status—working in unhealthy jobs, having poor health literacy and poor access to health services—may not necessarily be generalized [ 24 ]. Established theoretical explanations on migration and health can account for such differences: social and cultural patterns from the country of origin shape physical activity, body images, dietary intake, and food preferences [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Volhen and Rüesch reported that in the Switzlerland poor health and activities of daily living impairments were consistently associated with low socioeconomic status, low sense of mastery and little social support. Immigrant-specific preventive and health promotion initiatives should therefore target these immigrant groups [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Essa pesquisa me levou a muitas perguntas e gerou várias dúvidas. Nessa busca e em pesquisas posteriores foram achados diversos trabalhos que retratavam a situação dos refugiados e dos imigrantes dos países em conflito (Volken & Rüesch, 2014), os quais aportavam uma análise muito importante para compreender o que Gadamer (1977) nomeava como horizonte do outro, que é fundamental para fazer uma hermenêutica do conflito.…”
Section: Montesquieuunclassified